Purification, crystallization and preliminary X‐ray diffraction analysis of a soluble variant of the monoglyceride lipase Yju3p from the yeast Saccharomyces cerevisiae. Issue 2 (1st February 2015) - Rengachari, Srinivasan; Aschauer, Philipp; Sturm, Christian; Oberer, Monika
<x xml:space="preserve">Abstract</x> The protein Yju3p is the orthologue of monoglyceride lipases in the yeast Saccharomyces cerevisiae. A soluble variant of this lipase termed s‐Yju3p (38.3 kDa) was generated and purified to homogeneity by affinity and size‐exclusion chromatography. s‐Yju3p was crystallized in a vapour‐diffusion setup at 293 K and a complete data set was collected to 2.4 Å resolution. The crystal form was orthorhombic (space group P212121), with unit‐cell parameters a = 77.2, b = 108.6, c = 167.7 Å. The asymmetric unit contained four molecules with a solvent content of 46.4%.